Strategy for Improving Football Learning Outcomes Through the Implementation of Mini Football Games in Junior High School Students - Son Ikhlas Hulu; Alwi Fahruzy Nasution; Joko Priono (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This classroom action research aims to improve soccer learning outcomes through the implementation of mini soccer games for ninth-grade students of Madani Private Junior High School in the 2025/2026 Academic Year (n=32). The research was conducted in two cycles, each of which included planning, action, observation, and reflection. The learning action used small-sided games (mini soccer) 5 vs. 5 on a modified field (±25×35 m) with simple rules (no offside, kick-in) and player rotation to ensure high student engagement. Data collection used activity observations and skill practice tests with a passing and dribbling performance rubric (technical indicators; scale 1–4 per indicator) which were converted to a score of 0–100 with a KKM reference of 75. The results of cycle I showed an average score of 68.75 with a completeness of 56.25%, where passing and dribbling were not optimal. Improvements in cycle II were made through emphasizing basic technique training before the game and providing clearer tactical instructions. The results increased to an average of 81.56 with a completion rate of 87.50%, accompanied by increased student motivation, engagement, and social interaction during learning. Thus, mini-soccer games are effective as a learning strategy to improve soccer learning outcomes in junior high school students.